Adjuvant zoledronic acid reduces fractures in breast cancer patients; an AZURE (BIG 01/04) study. (May 2018) - Wilson, C.; Bell, R.; Hinsley, S.; Marshall, H.; Brown, J.; Cameron, D.; Dodwell, D.; Coleman, R.
Abstract: The fracture impact of adjuvant bisphosphonates in breast cancer is not defined with most trials reporting changes in bone mineral density as a surrogate. The AZURE trial (ISRCTN79831382) evaluated the impact of adjuvant zoledronic acid (ZOL) on fractures. The AZURE trial is an academic, multi-centre, randomised phase III study evaluating the addition of ZOL 4 mg to standard therapy (neo/adjuvant chemotherapy and/or endocrine therapy) for 5 years (administered by intravenous (iv) infusion every 3–4 weeks for 6 doses, then 3 monthly × 8 and 6 monthly × 5) in patients with stage II/III early breast cancer. Fracture data collected as part of skeletal-related adverse event reporting were analysed after a median of 84.2 months of follow-up and 966 disease-free survival (DFS) events. We assessed number of fractures, time-to-first fracture and the incidence of fractures before and after disease recurrence. Two hundred forty-four patients reported ≥1 fracture, 140 (8.3%) in the control arm (171 fractures) and 104 (6.2%) in the ZOL arm (120 fractures). Of the 291 fractures reported, 207 fractures occurred in the absence of recurrence (control 111, ZOL 96), 80 after recurrence (control 59, ZOL 21). The 5-year fracture rate was reduced from 5.9% (95%CI 4.8, 7.1%; control) to 3.8% (95%CI 2.9, 4.7%) with ZOL. ZOL significantly increased time-to-first fracture (HR 0.69, 95%CI 0.53–0.90; P = 0.0053) but the majority of fracture prevention benefit occurred after a DFS event (HR 0.3; 95%CI 0.17, 0.53; P < 0.001). Fracture benefits from ZOL were similar across menopausal sub-groups. In conclusion, adjuvant ZOL reduced the risk of clinical fractures, the majority of this protection occurred after disease recurrence. Highlights: This study represents the largest data collection of fracture incidence during adjuvant bisphosphonate use in breast cancer. The AZURE trial evaluated the addition of zoledronic acid (ZOL) 4 mg for 5 years to standard neo/adjuvant chemotherapy and/or endocrine therapy (control) in patients with stage II/III early breast cancer. Two hundred forty-four patients reported ≥1 fracture, 140 (8.3%) in the control arm (171 fractures) and 104 (6.2%) in the ZOL arm (120 fractures). The 5-year fracture rate was reduced from 5.9% (95% confidence interval [CI] 4.8, 7.1%; control) to 3.8% (95%CI 2.9, 4.7%) with ZOL. ZOL significantly increased time-to-first fracture (hazard ratio [HR] 0.69, 95%CI 0.53–0.90; P = 0.0053) but the majority of fracture prevention benefit occurred after a disease-free survival event (HR 0.3; 95%CI 0.17, 0.53; P < 0.001).